Preoperative Factors Associated with Postoperative Diabetes Insipidus after Transsphenoidal Pituitary Adenectomy - Koirala, Sagar; Bishokarma, Suresh; Gongal, Dinesh Nath (Nepal Journal of Neuroscience, 2019)
Transsphenoidal pituitary adenectomy is the gold standard method of treatment of pituitaryadenomas. Post-operative diabetes insipid sis one of the common complication of this procedure. In this study we have analyzed pre-operative factors that may be associated with onset of diabetes insipid us following this procedure. A retrospective study of five years was conducted in a tertiary neurosurgical center. Histologically proven cases of pituitary adenomas who underwent transsphenoidalpituitary adenectomy were included in the study. Age and sex of the patients along with size and functional type of tumor were analyzed to see if they predicted the occurrence of diabetesinsipidus post-operatively. Out of 49 cases who underwent transsphenoidalpituitary surgery, 46 cases were proven to be pituitary adenomas histologically. There was male preponderance with male to female ratio of2:1. Age ranged from 15 to 72 with median age of 37 years. Nonfunctional, prolactinomas and growth hormone secreting tumors, were 25, 16and 4 in number. Median size of the tumor was2.35 in largest diameter. Out of these patients13 (28%) patients developed diabetes insipid us. Age, sex of the patient, size of the tumor and functional type of the tumor did not predict the incidence. Age, sex of the patient, size of the tumor and functional type of the tumor do not predict the incidence of diabetes insipid us post-operatively in patients undergoing transsphenoidal pituitaryadenectomy.